Are health and social care professionals prepared for palliative care in parkinson's disease?. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Kernohan, W George; Waldron, Mary; Foster, Sue; Hasson, Felicity; Cochrane, Barbara
Abstract : Background: Although palliative care has been advocated in the care of patients with chronic diseases such as parkinson's disease (PD) they do not always receive it in a timely fashion. Aim: The authors sought to identify the health and social care professionals; self-assessed levels of training and confidence to deal with palliative care in PD. Methods: Within an exploratory research design, 32 health and social care professionals completed a survey on their levels of training and confidence in providing palliative care to people with PD. Descriptive statistical analysis was used to explore the data. Results: Nine doctors, nine nurses, seven Allied Health Professionals (AHPs) and seven social workers completed questionnaires. Half of the participants (n=16) had cared for over 30 patients with advanced PD. Over half (n=17, 53%), had received some training in both parkinson's disease and palliative care, while 13, (40%) had training in one or the other. Over half (n=17, n=53%) of participants were confident or very confident in managing or providing palliative care to patients with advanced PD. Four (13%) participants had low or no confidence in providing such care: three of this group were social care professionals. Those who had had training in PD (n=27 84%) tended to rate themselves as being more confident. Similarly, those who had training in palliative care (n=21, 66%) rated themselves as confident or very confident in providing palliative care to patients with PD and caregivers. Conclusions: Most respondents showed an acceptable level of readiness to manage and deliver palliative care in PD. Attendance at training sessions in PD and in palliative care leads to greater confidence in dealing with this condition.